Characterization of cellulase from Bacillus subtilis N15 - Choudhary, Dinseh (My University, 2013)
Bacillus subtilis N15 is an isolate from sugarcane bagasse was checked for carboxymethyl cellulose (CMCase) activity of cell free supernatant using 2% carboxymethyl cellulose. Optimum enzyme activity was 0.15 U/ml at pH 7.0 and 0.11 U/ml at 40⁰C. Crude cellulase from Bacillus sp. was stable at pH ranging from 5.0-7.0 and was thermally stable up to 50⁰C. The enzyme activity of the partially purified cellulases was higher at 30-90 mM MgSO4.7H20 and FeSO4.7H2O, while EDTA inhibited the enzyme activity. Cellulase was partially purified by ammonium sulphate precipitation and exhibited 6 fold increase in CMCase activity with a molecular weight of 35 kDa as confirmed by zymography
Master of Science-Microbiology-Dissertation
Keywords: cellulase; N15; SDS; Bacillus subtilis